DETERMINAN KEBERHASILAN REFORMASI SISTEM KEPEGAWAIAN DI CHINA PERIODE 1980-2010 - Ramadhani Haryo Seno (Politeknik STIA LAN Makassar, 2020)
Focus of this research is to describe civil service system reform process in one country, by finding the detreminants of successful factors in transforming and developing civil service system in China. Descriptive qualitative analysis by study literature and examining secondary data as a data collection method use in this research. The result show that there are four determinants of successful: political, legal, bureaucratic, and economic factors. Best practices can be adopted from every factor (1) The political factors such as commitment, consistency, and leadership ability (2) The legal factors such as; Related to the main rules, supervision, and approval, (3)The bureaucratic factors such as: professionalism, implementation of a merit system, and improving welfare, and (4) The economic factors such as: pragmatic policy selection and economic development that encourage investment